Mass transfer and concentration contours between an oblate spheroid buried in granular beds and a flowing fluid - J. M. P. Q. Delgado (2009)
The present work describes the mass transfer process between a moving fluid and a soluble oblate spheroid buried in a packed bed of small inert particles with uniform voidage. A general solution of this problem is not available analytically and in the present work we only consider the limiting cases of mass transfer with a thin concentration boundary layer, to which corresponds high values of Peclet number. The solution of this problem is useful in the analysis of a variety of physical situations, such as the analytical models of continuous injection of solute at a point source, in a uniform stream, to estimate the distance from the